The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/healthcare10010026
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Work Life as Predictors of Occupational Burnout of Nurses and Doctors in Operating Theaters in Poland—Multicenter Studies

Abstract: Introduction: Researchers’ interest in occupational burnout results primarily from the dangerous and extensive consequences of this phenomenon. The aim of the study was to analyze the level of occupational burnout among nurses and doctors in operating theaters. Materials and Methods: A cross-sectional survey study conducted on 325 nurses and doctors of seven hospitals in Poland. The Maslach Burnout Inventory (MBI) and the Areas of Worklife Survey (AWS) by Michael Leiter and Christina Maslach. Results: The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
(38 reference statements)
2
21
0
Order By: Relevance
“…Job satisfaction was predicted by the level of teachers' engagement in their workplace. These results add to the existing literature [24] that discusses areas of work life (e.g., workload, reward, community, control, fairness, and values being predictors of occupational burnout and satisfaction).…”
Section: The Effects Of Teachers' Work Values and Work Engagement On ...supporting
confidence: 59%
See 2 more Smart Citations
“…Job satisfaction was predicted by the level of teachers' engagement in their workplace. These results add to the existing literature [24] that discusses areas of work life (e.g., workload, reward, community, control, fairness, and values being predictors of occupational burnout and satisfaction).…”
Section: The Effects Of Teachers' Work Values and Work Engagement On ...supporting
confidence: 59%
“…As indicated in Sections 4.1-4.3 authors have described the rates of teachers' work values, work engagement, and job satisfaction during the pandemic. In comparison to the period before the outbreak of the pandemic, these results show a relatively higher result for teachers' work values (M = 4.39, SD = 0.55) compared to most of the pre-pandemic studies, which involved different employees, like physicians [19], bank managers [24], teachers [33], information professionals [44], and hotel managers [63], conducted in different countries including Greece, India, China, Italy, and Poland. However, with regards to teachers' age and their teaching experience, the current study is still in line with the previous studies, whereby the two biographical constructs showed a negative correlation to teachers' work values.…”
Section: Teachers' Work Values Work Engagement and Job Satisfactionmentioning
confidence: 70%
See 1 more Smart Citation
“…, 2019). Additionally, there is evidence that when emergency health workers feel treated unfairly or be systematically under-considered at work, they are more likely to experience burnout symptoms (Jarzynkowski et al. , 2022; Oliphant et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, outsider mistreatment is frequently viewed as part of the job, and outsider incivility is the most frequent form of mistreatment reported by emergency health workers (Touzet et al, 2019). Additionally, there is evidence that when emergency health workers feel treated unfairly or be systematically under-considered at work, they are more likely to experience burnout symptoms (Jarzynkowski et al, 2022;Oliphant et al, 2022). However, there are many unanswered questions to be addressed.…”
Section: Introductionmentioning
confidence: 99%